Islamic Religious Education Learning Methods fo Specially Intelligent Children. - Siti Maryam; Ilzamudin Ma'mur; Muhajir Muhajir (UIN Sunan Gunung Djati Bandung, 2022)
The method of Islamic Religious Education is actually very necessary in fostering the character of special intelligent students. But sometimes teachers have not empowered methods and approaches to learning properly and effectively. As a result, the goals of Islamic religious education have not been achieved as expected. Likewise, Islamic religious education learning at SMAN 11 Sepatan Tngerang has not been able to develop the character education of ci students to the fullest, because the method used is still classified as conventional, namely learning by lecture and discussion methods, there are no visible variations of the model carried out, it has not touched the psychological realm of students. ci. So the problem of method in learning needs to include ctl and inquiry methods as well as an Islamic psychopedagogical approach, so that the learning of Islamic religious education does not occur boredom. Where the use of appropriate and varied Islamic religious education methods in learning will color the attitudes and behavior of CI students in learning, and also affect other intelligences possessed by students. Islamic Religious Education aims to make servants of Allah who are obedient to worship, knowledgeable, noble and have good skills, and have physical and spiritual health. so that it can provide solutions to the problems of character education for ci students.This study uses a qualitative method.by collecting data from observations, interviews and documentation. The results of this study are able to provide offers to overcome problems and solutions in overcoming the method of character education for ci students at SMAN 11 Sepatan Tangerang.attention during learning. The results of this study are expected to contribute and provide solutions to the teaching of Islamic religious education at SMAN 11 Sepatan, Tangerang.Keywords: Learning methods. Student Character. Special Smart